Aerosol distribution change in the Antarctic winter─Balloon born experiment during 1991─(abstract) - Hayashi, Masahiko; Iwasaka, Yasu-nobu (National Institute of Polar Research, 1993)
P(論文) Stratospheric aerosol concentrations and size distributions were observed during the Antarctic winter by balloon borne particle counter in the 32th Japanese Antarctic Research Expedition (JARE-32). Four balloons were launched at Syowa Station (69 departmental bulletin paper